2019
DOI: 10.1161/circulationaha.119.040180
|View full text |Cite
|
Sign up to set email alerts
|

Novel Drug Targets for Ischemic Stroke Identified Through Mendelian Randomization Analysis of the Blood Proteome

Abstract: Background: Novel, effective, and safe drugs are warranted for treatment of ischemic stroke. Circulating protein biomarkers with causal genetic evidence represent promising drug targets, but no systematic screen of the proteome has been performed. Methods: First, using Mendelian randomization (MR) analyses, we assessed 653 circulating proteins as possible causal mediators for 3 different subtypes of ischemic stroke: large artery atherosclerosis, cardioe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
88
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 49 publications
5
88
1
Order By: Relevance
“…Previous studies have also leveraged the increased availability of pQTL data for drug target and biomarker discovery [12][13][14][15][16][17][18]. For example, in one of the largest pQTL studies to date, Sun et al [14] applied an aptamer-based approach (rather than an antibody-based assay as here) to perform extensive co-localization analyses and used MR to assess the causal contribution of IL1RL1-IL18R1 locus to atopic dermatitis, and that of MMP12 to coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also leveraged the increased availability of pQTL data for drug target and biomarker discovery [12][13][14][15][16][17][18]. For example, in one of the largest pQTL studies to date, Sun et al [14] applied an aptamer-based approach (rather than an antibody-based assay as here) to perform extensive co-localization analyses and used MR to assess the causal contribution of IL1RL1-IL18R1 locus to atopic dermatitis, and that of MMP12 to coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…32 In this study, genetically determined FXI levels were identified as one of five causal mediators of ischemic stroke, with the cardioembolic subtype appearing to drive this effect. 32 In both studies, no adverse side effects appeared to be linked to the genetic influences on variation in FXI levels, providing further justification for clinical trials on FXI-related interventions in the context of ischemic stroke. 32 In light of our findings that stroke patients with high FXI:C had a higher risk for secondary events after first stroke, the population of stroke patients with high FXI levels may particularly benefit from such interventions, and FXI:C may be a useful biomarker in identifying individuals who are most likely to benefit from such interventions.…”
Section: Discussionmentioning
confidence: 91%
“…In summary, all these ndings show that human genetic variants could be used to repurpose the existing targets for new therapeutic uses [7,16,[20][21]. However, it is largely unknown about the role of rs7529229 in IS, which promotes us to perform a comprehensive analysis.…”
Section: Introductionmentioning
confidence: 99%